Pengembangan Sistem Online Public Access Catalog Perpustakaan dengan Fitur Tracking Minat Baca - Kordinal Depriansyah; Angga Bayu (Institut Teknologi Garut, 2026)
School library digitalization is generally limited to operational circulation aspects without exploring user behavior data. At SMA IT Quran Qordhova, the conventional system hindered search efficiency and made it difficult to map students’ reading interests. This study aims to develop a web-based Online Public Access Catalog (OPAC) system integrated with a user activity tracking feature. The system was developed using the CodeIgniter 4 framework with the Waterfall methodology. Black Box testing results on 80 functional scenarios showed a 100 percent success rate in interface functionality execution. The main contribution of this study lies in the automatic recording of query logs and click interactions, which are visualized through a descriptive analytics dashboard, as well as the integration of the WhatsApp API to improve the efficiency of circulation administration processes. This system provides an initial empirical foundation for school administrators in formulating library collection procurement policies that are adaptive to students’ reading interests.